Agronomic characteristics of nagara sweet potatoes (Ipomoea batatas L.) from south kalimantan wetlands - Apriani, Rila Rahma; Nugroho, Agung; Adriani, Dewi Erika; Purnomo, Joko (Jurnal AGRO, 2025)
Understanding the agronomic characteristics of sweetpotato grown in wetland is critical to optimise cultivation and maximise yield. By studying factors such as plant morphology and yield, as well as environmental conditions, is important to identify varieties and cultivation practices that are most suitable for specific agroecological zones. This research aims to study the agronomic characters of nagara sweet potato in South Kalimantan’s wetlands and identify abiotic factors that support its growth. A total of 15 sweet potato accessions were randomly sampled in sweet potato cultivation hotspot areas in July 2024. Hierarchical cluster analysis was conducted to see the similarity of the accessions found. The results showed that the agronomic characters of sweet potato accessions differed from the registered variety (Ubi Nagara KB-1), especially in characteristics type & number of leaf lobes, shape and number of tubers. Sweet potato yield was also found to be lower (14 t ha-1) compared to Ubi Nagara KB-1 (20 t ha-1). Abiotic data were found to be favourable for sweet potato agronomy, except for pH. The accessions found are still recommended to be developed in lebak swamp land, due to their adaptability and potential which is still higher than sweet potato in general (in dry land). Genetic testing is needed to prove that morphological differences are caused by different varieties (genetic) or decreased environmental conditions. ABSTRAK Karakteristik agronomi ubi jalar yang ditanam di lahan basah sangat penting dipelajari untuk mengoptimalkan budidaya dan memaksimalkan hasil panen. Pemahaman faktor-faktor seperti morfologi dan hasil tanaman, serta kondisi lingkungan, penting untuk mengidentifikasi varietas dan praktik budidaya yang paling sesuai untuk zona agroekologi tertentu. Penelitian ini bertujuan mempelajari karakter agronomi ubi nagara di lahan rawa lebak Kalimantan Selatan dan mengidentifikasi faktor abiotik yang mendukung pertumbuhannya. Sebanyak 15 aksesi ubi jalar diambil secara acak di area sentra budidaya ubi pada Juli 2024. Analisis kluster hierarki dilakukan untuk melihat kekerabatan aksesi yang ditemukan. Hasil penelitian menunjukkan bahwa karakter agronomi aksesi ubi jalar berbeda dengan varietas yang terdaftar (Ubi Nagara KB-1), terutama pada ciri tipe, jumlah cuping daun, bentuk dan jumlah umbi. Hasil ubi jalar juga ditemukan lebih rendah (14 t ha-1) dibandingkan dengan Ubi Nagara KB-1 (20 t ha-1). Data abiotik ditemukan mendukung agronomi ubi jalar, kecuali pH. Aksesi yang ditemukan masih direkomendasikan untuk dikembangkan di lahan rawa lebak, karena adaptabilitas dan potensinya yang masih lebih tinggi dibanding ubi jalar secara umum (di lahan kering). Uji genetik diperlukan untuk membuktikan perbedaan morfologi disebabkan oleh varietas berbeda (genetik) atau penurunan kondisi lingkungan.